2019
DOI: 10.1038/s41419-019-1317-7
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon attenuates DNA damage-induced apoptosis by regulating the transcription-independent function of p53

Abstract: Cereblon (CRBN) is the substrate receptor of the cullin 4-RING E3 ligase complex and has been employed for targeted protein degradation in the treatment of cancers. However, its normal physiological functions and molecular mechanism in the regulation of DNA damage response are largely unknown. Here we find that CRBN plays a protective role against DNA damage-induced apoptosis in cell lines and primary cells. Mechanistic studies demonstrate that although CRBN does not affect the ubiquitination and degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Recently, it has been discovered that CRBN inhibits DNA damage-induced apoptosis (Zhou and Xu, 2019). However, it is unknown whether and how death receptors regulate CRBN and its function.…”
Section: Crbn Is Decreased In Hela and Nci-h1688 Cells Upon Trail Trementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been discovered that CRBN inhibits DNA damage-induced apoptosis (Zhou and Xu, 2019). However, it is unknown whether and how death receptors regulate CRBN and its function.…”
Section: Crbn Is Decreased In Hela and Nci-h1688 Cells Upon Trail Trementioning
confidence: 99%
“…Because activated CASP-8 could cleave BID (Li et al, 1998;Luo et al, 1998), BID cleavage or reduction could serve as an indicator to demonstrate the activation of death receptor and CASP-8 (Chou et al, 1999). In our previous study, we found that CRBN inhibits the etoposide-induced intrinsic apoptosis (Zhou and Xu, 2019). However, it is unknown whether CRBN is involved in the death receptor-induced extrinsic apoptotic pathway and whether modulation of caspase activity could regulate the biological function of CRBN.…”
Section: Introductionmentioning
confidence: 98%
“…CRBN KO mice have been characterized in multiple phenotypical contexts. A series of studies elucidating the physiological function of CRBN has also been reported in various disease models or under specific challenges [ 15 , 24 , 29 31 ]. The deficiency of CRBN has exhibited protective effects or positive influence under various adverse challenges in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The silencing of CRBN impaired the ability of lenalidomide to induce p21 expression, indicating that lenalidomide directly inhibits CLL cell proliferation in a CRBN/p21-dependent manner [ 23 ]. Recently, p53 was reported to be a direct substrate of CRBN, yet subcellular distribution, protein expression level, and ubiquitination were not significantly affected [ 24 ]. In the interim, our research group reported that the permanent cell line of mouse embryonic fibroblast (MEF) that lacked CRBN was strongly resistant to hydrogen peroxide (H 2 O 2 ), which is a typical ROS inducer for activating cellular senescence, and the loss of CRBN exhibited the pre-activation of p38 MAPK [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that CRBN can control mitochondrial homeostasis through regulating ECSIT, which is essential for stabilization of mitochondrial complex I and ROS. Furthermore, CRBN binds p53 and hinders its interactions with the anti-apoptotic mitochondrial protein B-cell lymphoma 2/B-cell lymphoma-extra Large (Bcl-2/Bcl-xL) ( 13 ). Overall, the above results support the theory that CRBN prevents oxidative damage-induced cell death through facilitating maintenance of mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 99%